PENGGUNAAN REWARD STICKER DALAM PENANAMAN SIKAP DISIPLIN ANAK - Miratul Hayati; Dian Rifatul Wafa (stit-islamic-village, 2021)
This study aims to explore the use of reward stickers in instilling discipline in early childhood. The research uses a qualitative approach using the case study method. The subjects in this study were TK B class teachers Waladun Solihun Tangerang Banten and TK B class children who used reward stickers in learning activities. We collected data through techniques, interview observations, and documentation. Data analysis using Miles Huberman with stages of data reduction, data presentation, verification and drawing conclusions. The results of the study explain that the use of reward stickers can be explored in (1) the type of reward given by the teacher in learning activities (2) the strategy in giving reward stickers (3) giving reward stickers in motivating children (4) aspects of discipline developed (5) response children in giving reward stickers (6) when giving reward stickers. This study recommends the use of reward stickers to improve children's discipline.